Environmental distribution of coral-associated relatives of apicomplexan parasites - Janouškovec, Jan (Nature Publishing Group, 2013)
A lineage of plastid-bearing eukaryotic microbes that is closely related to apicomplexan parasites was recently found in a specific association with coral reefs (apicomplexan-related lineage-V, or ARL-V). Here, we address the possible nature of this association using plastid ‘contamination' in fine-scale bacterial sequence surveys. In a transect between corals and associated macroalgae, ARL-V is specifically associated with the coral, in contrast to all microalgal types (including diatoms, haptophytes, pelagophytes and photosynthetic apicomplexan relatives, Chromera and Vitrella), which are associated with macroalgae. ARL-V is associated with at least 20 species of symbiotic corals through extended time periods and large geographic distances. It is significantly enriched in healthy coral tissue and shallow reef depths. Altogether, the evidence points to a specific relationship between ARL-V and corals, and is suggestive of symbiosis, perhaps based on photosynthesis.